2018
DOI: 10.14393/bj-v34n2a2018-39701
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of morphological traits for grain yield in common bean

Abstract: In Brazil, the common bean crop has representative agricultural exploitation, not only because of its production economic value, but also because there is a large cultivation area. This research aimed to investigate the direct and indirect relationship of morphological components on grain yield in common bean plants. This study was carried out in a Quartzarenic Neosol in the municipality of Cassilândia, Mato Grosso do Sul State, Brazil, in the agricultural year of 2016/2017. The evaluated traits were: grains y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 7 publications
1
8
0
2
Order By: Relevance
“…Figure 3 expresses the network of Pearson's correlations among morphological variables. The efficiency of such innovative technique to relate many variables has already been highlighted in the literature by Silva et al (2017a, b), Oliveira et al, (2018), andOliveira et al, (2019).…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…Figure 3 expresses the network of Pearson's correlations among morphological variables. The efficiency of such innovative technique to relate many variables has already been highlighted in the literature by Silva et al (2017a, b), Oliveira et al, (2018), andOliveira et al, (2019).…”
Section: Resultsmentioning
confidence: 94%
“…Determination coefficients above 0.70 are considered high. Authors such as Silva et al, 2017b, Teodoro et al, 2015, Oliveira et al, 2018, and Oliveira et al, 2020 have also found coefficients of determination higher than 0.70. 5.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…O coeficiente de correlação de Pearson é uma ferramenta bastante utilizada para expressar, por meio de um valor puro, a associação entre duas variáveis quantitativas. Entretanto, essa medida é insuficiente para explicar uma relação de causa e efeito (Blind et al, 2018), uma vez que outras podem estar interferindo nessa relação (Oliveira et al, 2018;Sari et al, 2018), conduzindo o pesquisador a conclusões errôneas pela obtenção de valores superestimados.…”
Section: Introductionunclassified
“…Autores como Oliveira et al, 2018e Oliveira et al, 2020a, estudaram características biométricas de culturas agrícolas e destacam a sua importância para entendimento do comportamento da planta em função do manejo implementado na cultura, seja ele hídrico ou nutricional. De acordo com Soares et al (2017), fatores como a disponibilidade hídrica, ciclo da cultura, espaçamento, época de semeadura, boas condições nutricionais e uma população entre 30.000 e 90.000 plantas ha -1 , são essenciais para que a cultura do milho atinja seu potencial máximo de produção.…”
Section: Introductionunclassified